2022
DOI: 10.3390/v14071582
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of CMV or 2b-Deficient CMV-Infected dcl2dcl4 Reveals the Effects of Viral Infection on Symptom Induction in Arabidopsis thaliana

Abstract: Due to the impaired antiviral RNAi, the dcl2dcl4 (dcl2/4) mutant is highly susceptible to viruses deficient of the viral suppressor of the RNA silencing (VSR) contrast to wild-type Arabidopsis. It was found that more severe disease symptoms were induced in dcl2/4 infected with VSR-deficient CMV (CMV-Δ2b or CMV-2aTΔ2b) compared to wild-type Arabidopsis infected with intact CMV. In order to investigate the underlying mechanism, comparative transcriptome analysis was performed with Col-0 and dcl2/4 that were infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Previous analysis of the transcriptomic response against CMV infection indicated a strong deregulation of gene expression with multiple molecular functions affected that included metabolic processes, transcription factor binding, hormone signaling and photosynthesis-associated processes 50,51 . Our RNA sequencing analysis (Sup Fig 3a) indicated that a substantial number of genes were differentially expressed (adjusted p-value <0.05, herein DEGs) under CMV infection: 886 and 723 at 10 and 20 dpi, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of the transcriptomic response against CMV infection indicated a strong deregulation of gene expression with multiple molecular functions affected that included metabolic processes, transcription factor binding, hormone signaling and photosynthesis-associated processes 50,51 . Our RNA sequencing analysis (Sup Fig 3a) indicated that a substantial number of genes were differentially expressed (adjusted p-value <0.05, herein DEGs) under CMV infection: 886 and 723 at 10 and 20 dpi, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous analysis of the transcriptomic response against CMV infection indicated a strong deregulation of gene expression with multiple molecular functions affected that included metabolic processes, transcription factor binding, hormone signaling and photosynthesis-associated processes 50,51 . Our RNA sequencing analysis (Sup Fig.…”
Section: Resultsmentioning
confidence: 99%